ISLAM DAN LEMBAGA KEUANGAN SYARIAH - Rizki Dian Mensari; Ahmad Dzikra (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2017)
Economic system of Islam is inseparable from banks and financial institutions. The financial institution is an identity in the economic system and is an instrument that applies the rules in the economic system itself. Though banking kovensional has become a major part in the running of the wheel of the economy but there are still many among the scholars stated that interest earned from banking activities not in accordance with Islamic teachings. In line with that of the last emerging financial institutions in the economic concept known as the Islamic banking Shariah, but in fact the users of banking services, as well as many of the Shari'a to non-Muslims. The financial institution is the main part of the financial system in a modern economy that serves the community of financial services users. With the help of financial institutions the businessmen can do a large amount of financial transactions that are not possible in cash.